Participatory development of a methodology for identifying potential areas of hydric recharge in hydrological sub-basins, applied to the Jucuapa river sub-basin, in Matagalpa, Nicaragua - Matus Silva, Oscar D. (2007)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2007